Climate change policy support, intended behaviour change, and their drivers largely unaffected by consensus messages in Germany. (August 2021) - Tschötschel, Robin; Schuck, Andreas; Schwinges, Alexandra; Wonneberger, Anke
Abstract: How can communication contribute to reducing greenhouse gas emissions through behaviour change and policy support? The existing literature emphasises informing people about the scientific consensus on climate change, but the underlying research has been conducted mainly in the US, where prior beliefs in human-made climate change are lower than in many other countries with the highest per-capita emissions. We test consensus messages in an 'extended gateway belief model' using a pre-registered survey experiment on a representative quota sample of the German population ( N = 1171). Our data show that consensus messages are likely to have no or only minimal effects on perceived scientific agreement, intended behaviour change and policy support. Still, in line with prior research, we find that perceived scientific agreement, belief in climate science, efficacy beliefs, and worry about climate change predict policy support and intended behaviour change. These results demonstrate that effective communication needs tailoring to its local context. Highlights: Key beliefs about climate change largely unaffected by consensus messages in Germany Structure of key beliefs about climate change consistent with gateway belief model Personal efficacy beliefs strongly predict intended behaviour change Political efficacy beliefs strongly predict policy support